Diversidade cultural e racial: desdobramentos da lei 10639/2003 nas práticas escolares do Estado de São Paulo - Leite, Valderlei Furtado (2010)
According to the approval of Law 10.639/2003, endorsed on January 9, 2003, it becomes mandatory to teaching History and culture Afro-Brazilian and African for Elementary and High school, establishing the need for new Brazilian Curricular Directives. This law was a result of class-conflict that indicated the disqualified aspects that were handled Brazilian education in relation to History and culture Afro Brazilian and African. It is believed that a better approach based on historical knowledge, anthropological, sociological and political will contribute significantly to provide a new vision about these subjects to Brazilian students and consequently increase the self-esteem to encourage the black segment of population. Law 10.639/03 is one of the most victories from the conflict of classes, to be due by the violent way that negroes were treated in the past, and even nowadays mark profoundly the future of children, youth and adults generations who are in schools, especially in the public school where the inclusion of History and Culture Afro-Brazilian and African in Curricular Directives will help them. Identifying the importance of the issue to the awareness of ethnical relations, we seek by this research discussing issues related to the effective implementation in São Paulo schools and analyze the main aspects of the law, commenting on it. For a better comprehension of the issues we will approach the multiculturalism and the educative praxis oriented to the multicultural way. It is important to clarify that the preoccupation on culture differences, the cultural plurality and the multiculturalism are being emphasized to national directives focusing the Basic education after the publishing of the referred law. The study was conducted by a research bibliography based on books, articles and Internet, it was developed by an exploratory qualitative research, in order to achieve the goal and the relevant information about the deployment of Law 10639/2003 in school practices and analyze how, in view teachers, employees who work in educational workshop deal with teaching culture African-Brazilian in São Paulo schools, Grande ABC , Paulista coast and Countryside